Fenólicos totais, polifenoloxidade e coloração em abacate ‘fuerte’ submetido a hidrotermia - Fumes, Joana Giffoni Figueiredo [UNESP]; Daiuto, Érica Regina [UNESP]; Cábia, Nathalie Cardoso [UNESP]; Vieites, Rogério Lopes [UNESP]; Carvalho, Lídia Raquel de [UNESP] (My University, 2011)
Avocado is a fruit highly perishable with limitations to the processing and subsequent storage, mainlydue to the fast pulp darkening. The objective of this research was to evaluate the hydrothermaltreatment effect, in 'fuerte' avocado, as for the total phenolic content, polyphenoloxdase enzymeactivity and color, correlating these parameters. Selected fruits was submitted hydrothermaltreatment to 45ºC for 5, 10, 15 and 20 minutes being maintained under refrigeration (10 ± 1 ºC and90±5% UR), and appraised for 15 days. Total phenolic contents increased to the 6th day of storage,decreasing starting from this moment, not happening difference among the treatments.Polyphenoloxdase enzyme activity decreased during the storage and it was inferior in controltreatment. There was not significant correlation for total phenolic content, polyphenoloxdase enzymeactivity and coloration. Fruits postharvest quality, in what it refers to the appraised parameters in thisresearch, it was higher for control treatment.

O abacate é um fruto altamente perecível, com limitações ao processamento e posteriorarmazenamento, principalmente devido ao rápido escurecimento da polpa. O objetivo desta pesquisafoi avaliar o efeito da hidrotermia, em abacate ‘fuerte’, quanto ao conteúdo de fenólicos totais,atividade da enzima polifenoloxidase e cor, correlacionando estes parâmetros. Os frutos selecionadosforam submetidos a tratamento hidrotérmico a 45ºC por 5, 10, 15 e 20 minutos sendo mantidos sobrefrigeração (10 ± 1 ºC e 90±5% UR), e avaliados durante 15 dias. O conteúdo de fenólicos totaisaumentou até o 6º dia de armazenamento, descrescendo a partir deste momento, não ocorrendodiferença entre os tratamentos. A atividade da enzima polifenoloxidase diminuiu durante oarmazenamento e foi inferior no tratamento controle. Não houve correlação significativa para aatividade da enzima polifenoloxidase, conteúdo de fenólicos totais e coloração. A qualidade póscolheita dos frutos, para os parâmetros avaliados nesta pesquisa, foi superior para o tratamentocontrole.
Total phenolics, polyphenoloxidase and coloration in ‘fuerte’ avocado submitted to thermal treatment
Keywords: Persea americana Mill; Darkening; Postharvest; Persea americana Mill.; Escurecimento; Pós-colheita